2019
DOI: 10.3389/fnagi.2019.00350
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Spontaneous Brain Activity Patterns in Different Biologically-Defined Alzheimer’s Disease Cognitive Stage: A Preliminary Study

Abstract: Background: The National Institute on Aging-Alzheimer's Association (NIA-AA) has proposed a biological definition of Alzheimer's disease (AD): individuals with both abnormal amyloid and tau biomarkers (A+T+) would be defined as AD. It remains unclear why different cognitive status is present in subjects with biological AD. Resting-state functional magnetic resonance imaging (rsfMRI) has provided an opportunity to reveal the brain activity patterns in a biologically-defined AD cohort. Accordingly, we aimed to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 57 publications
2
20
1
Order By: Relevance
“…Since the precuneus, along with the PCC, is well-known as an essential component of the DMN and brain network hub, it may be the earliest region showing the detrimental effect of Aβ cascade. On the other hand, our findings contradicted previous research by Zeng et al (37), which showed that fALFF values in the inferior frontal gyrus (IFG) were higher in cognitively normal adults with Aβ+ than those with Aβ−. Zeng et al speculated that, under the impact of Aβ pathology, increased neural activity in the IFG could be a compensational effect in an effort to maintain normal cognitive performance.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Since the precuneus, along with the PCC, is well-known as an essential component of the DMN and brain network hub, it may be the earliest region showing the detrimental effect of Aβ cascade. On the other hand, our findings contradicted previous research by Zeng et al (37), which showed that fALFF values in the inferior frontal gyrus (IFG) were higher in cognitively normal adults with Aβ+ than those with Aβ−. Zeng et al speculated that, under the impact of Aβ pathology, increased neural activity in the IFG could be a compensational effect in an effort to maintain normal cognitive performance.…”
Section: Discussioncontrasting
confidence: 99%
“…In line with our findings, rs-fMRI has consistently demonstrated decreased FC of the precuneus (17,36). Furthermore, a more recent study showed that subjects with Aβ pathology had significantly lowered fALFF in the bilateral PCC and precuneus (37). Since the precuneus, along with the PCC, is well-known as an essential component of the DMN and brain network hub, it may be the earliest region showing the detrimental effect of Aβ cascade.…”
Section: Discussionsupporting
confidence: 91%
“…The frontal lobe may be an essential area of cognitive maintenance associated with AD (Zeng et al, 2019). In terms of cognitive function, it may be involved in episodic memory and working memory (de Chastelaine et al, 2011;Matthews, 2015).…”
Section: Similar Pattern Between the Obj-scd And Amci Groupsmentioning
confidence: 99%
“…Abnormalities in dynamic brain activity, including excessive variability (increased dALFF) and excessive stability (decreased dALFF), impair brain function (Christoff et al, 2016). These methods have been widely used in neurodegenerative diseases, like AD (Yang et al, 2018;de Vos et al, 2018;Li et al, 2019;Zeng et al, 2019), Parkinson's disease (Skidmore et al, 2013;Zhang et al, 2019) have been proven feasible and effective. Thus, combining the sALFF and dALFF may help to illuminate the underlying brain functional changes in SNAP.…”
Section: Introductionmentioning
confidence: 99%